Propensity to high-fat diet-induced obesity in rats is associated with changes in the gut microbiota and gut inflammation - de La Serre, Claire Barbier (American Physiological Society, 2010)
Consumption of diets high in fat and calories leads to hyperphagia and obesity, which is associated with chronic “low-grade” systemic inflammation. Ingestion of a high-fat diet alters the gut microbiota, pointing to a possible role in the development of obesity. The present study used Sprague-Dawley rats that, when fed a high-fat diet, exhibit either an obesity-prone (DIO-P) or obesity-resistant (DIO-R) phenotype, to determine whether changes in gut epithelial function and microbiota are diet or obese associated. Food intake and body weight were monitored daily in rats maintained on either low- or high-fat diets. After 8 or 12 wk, tissue was removed to determine adiposity and gut epithelial function and to analyze the gut microbiota using PCR. DIO-P but not DIO-R rats exhibit an increase in toll-like receptor (TLR4) activation associated with ileal inflammation and a decrease in intestinal alkaline phosphatase, a luminal enzyme that detoxifies lipopolysaccharide (LPS). Intestinal permeability and plasma LPS were increased together with phosphorylation of myosin light chain and localization of occludin in the cytoplasm of epithelial cells. Measurement of bacterial 16S rRNA showed a decrease in total bacterial density and an increase in the relative proportion of Bacteroidales and Clostridiales orders in high-fat-fed rats regardless of phenotype; an increase in Enterobacteriales was seen in the microbiota of DIO-P rats only. Consumption of a high-fat diet induces changes in the gut microbiota, but it is the development of inflammation that is associated with the appearance of hyperphagia and an obese phenotype.